EFEK FUNGISTATIS, FUNGISIDAL EKSTRAK KAYU MANIS TERHADAP CANDIDA ALBICANS DAN EFEK BAKTERISTATIS BAKTERISIDAL TERHADAP STAPHYLOCOCCUS AUREUS DARI DENTURE STOMATITIS - Minasari Minasari; Dennis Dominika (Poltekkes Kemenkes Medan, 2017)
Cinnamon is one of the spices that has been used for a long time, even before 2100 BC as an essential material to mummify a king's body and also as addition for foods and drinks to increase the flavours. Cinnamon has three active components such as cinnamaldehyd, eugenol and linalool. Cinnamon has good fungicidal and fungistatic effect against Candida albicans and bacteristatic, bactericidal effect against Staphylococcus aureus. Cinnamon can be used to decrease the amount of Candida albicans and Staphylococcus aureus colonies, so the researcher is interested to examine the fungistatic, fungicidal, bacteristatic dan bactericidal effect against Candida albicans and Staphylococcus aureus. The goal of this research is to determine the effect of different concentrations of cinnamon extract against Candida albicans and Staphylococcus aureus.In this research, the extract's concentrations that are used are 100%, 50%, 25%, 12,5%, 6,25%, 3,125%, 1,56%, 0,78%, 0,39%, 0,195% and also two controls which are formaldehyd and aquadest. The extract used in this research is obtained by extraction method. Dilution technique is used in the test with three times replication. This research is experimental laboratorium type with pretest-postest design. Kruskal-Wallis and Mann-Whitney test is used to analyze the data.The result show that concentration 0,78 % extract has shown fungistatic effect and concentration 25% has shown fungicidal effect against Candida albicans, and concentration 1,562% bacteristatic, concentration 50% bactericidal Staphylococcus aureus. From double comparison table, we can conclude that there are significant difference between each concentration's effect against Candida albicans and Staphylococcus aureus.The result shows that the increase of cinnamon extract's concentration will lessen the remaining colonies of Candida albicans.